Analisis Kalium, Kalsium Dan Natrium Dalam Buah Merah (Pandanus baccari) Asal Kabupaten Poso Sebagai Alternatif Peluruh Batu Ginjal - Yulianti, Iluh Devi; Walanda, Daud K.; Said, Irwan (Jurnal Akademika Kimia, 2015)
Red fruit (pandanus baccari) founded in Poso District was not familiar by many people. Red fruit contains chemicals that can be used as a traditional medicine for a wide variety of treatments. The purposes of this study were to analyze the content of potassium, calcium, and sodium in the extract of red fruit, and the solubility of calcium in the extract. Concentration of the extract was varied to 1%, 2%. 4%, and 6% to test the solubility of the calcium. Solubility of calcium in the extract of red fruit was determined by using atomic absorption spectrophotometer (AAS). The results showed that the extract of red fruit contained 30.35 ppm, 58.24 ppm, and 50.00 ppm of potassium, calcium, and sodium, respectively. Results of the solubility test of calcium in the extract showed that higher the concentration affected to the greater solubility. This can be seen from the difference between the lowest concentrations to the highest concentration in a row at 29.446 ppm, to 78.856 ppm, to 189.446, to 285.016 ppm. Thus it can be concluded that the extract of red fruit was possible to dissolve kidney stones.